Numerical Solution of Eikonal Equation Using Finite Difference Method - Alotibi, Sana’a Abdullah (JOURNAL OF ADVANCES IN MATHEMATICS, 2018)
In this paper, a method to calculate tsunami wave front is introduced using the finite difference method to solve the ill-posed problem and to calculate perturbed velocity of the wave front. Comparison between the actual and approximate solution will be proposed in a table form and a graphic form.